Fear of Failure vs Growth Mindset: Obstacle or Accelerator to the Courage to Start a Business? - Damas Gianlugi Alrizqi; Siti Nardiyah Muhrami; Nurul Haeriyah Ridwan; Edy Suryanto; Sumiati Tahir (Journal of Economics Education and Entrepreneurship, 2026)
This study aims to analyze the influence of fear of failure and growth mindset on the courage to start a business among economics students in Makassar, with entrepreneurial self-efficacy as a mediating variable. The study employs an explanatory quantitative approach and uses a cross-sectional survey of 150 purposively selected respondents. Data analysis was performed using SEM-PLS in WarpPLS 8.0. The results showed that a growth mindset had a positive effect on entrepreneurial self-efficacy and the courage to start a business, and entrepreneurial self-efficacy had a positive impact on the courage to start a business. Conversely, fear of failure had no significant effect on either entrepreneurial self-efficacy or the courage to start a business. The mediation test confirmed that entrepreneurial self-efficacy mediates the impact of growth mindset on the courage to start a business, but does not mediate the effect of fear of failure. These findings emphasize the importance of strengthening a growth mindset and self-efficacy to encourage students to take the courage to start a business.